E-contract in the Aspect of Online Sale and Purchase Agreement Correlated with Article 1320 of the Civil Code - Risma Satriana Nilamjati; Albertus Sentot Sudarwanto; Yudho Taruno Muryanto (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
When engaging in online transactions, it is highly challenging to guarantee adherence to the legal stipulations of the agreement. This challenge arises because online transactions occur via the Internet, meaning that the involved parties do not interact face-to-face, and the majority of online sales agreements are not documented in writing. The facets of